Bioactive Compound Chemistry and Antiasthmatic Activity of Betulinic Acid and Taraxerol in Experimental Models - Narayan, Shiv; Krishna, Gaurav; Mishra, Raghav (Current Topics in Medicinal Chemistry, 2025)
BackgroundThe natural molecules betulinic acid (BA) and taraxerol (T) have many biological and therapeutic uses, one of which is the relief from asthma symptoms. This study wasThis study aimed to assess BA and T effectiveness in treating bronchial asthma and perform a molecular docking study to find the binding energy of BA and T with β-adrenoceptor.MethodsUsing ethanol as the solvent, the Bacopa monnieri leaves were extracted using a soxhlet equipment. As a reference medicine, budesenoid was utilised. With PyRx 0.8, the molecular docking experiment was conducted using AutoDock vina. The protocol followed by the acute toxicity study was the OECD guideline 425. The effectiveness of the test medication in alleviating asthma was determined using an anaphylactic microshock model in guinea pigs.ResultsMolecular docking analysis showed high binding affinities of BA (-7.95 kcal/mol) and T (-8.23 kcal/mol) to LOX-5, which could suppress the synthesis of leukotriene, one of the central mediators of asthma pathogenesis. In vivo study, the BA and T treatment prolonged pre-convulsion time in guinea pigs up to 506.66 seconds as compared with the control (406.6 seconds, p < 0.05). This suggests protection against bronchial hyperresponsiveness. ELISA assays demonstrated that BA and T decreased the levels of TNF-α and increased IL-10, indicating a potential modulation of inflammation (p < 0.05). Markers of oxidative stress were lowered in treated animals, as demonstrated by the lowered MDA and enhanced activities of antioxidant enzymes such as SOD, CAT, and GSH, suggesting a protective effect against oxidative lung damage (p < 0.05). Histological analysis confirmed a decrease in inflammatory cell infiltration and airway remodeling in the treated groups compared to the OVA-induced controls.ConclusionThe results of the animal studies showed that BA and T reduced anaphylaxis, suggesting that it could be a viable alternative to current asthma treatments in the future. The results of the molecular docking investigation, however, showed that BA and T may indeed bind to the target receptor, opening the door to new treatment possibilities.
Keywords: adrenoceptor